Penggunaan Teknologi Pembelajaran Video Interaktif dalam Meningkatkan Kemampuan Berpikir Kritis Siswa pada Mata Pelajaran Al-Qur’an dan Hadits di kelas XI MAN 2 Garut - Munna Khoirunnisa; Masripah; Nenden Munawaroh; Fiqra Nazib (Advances In Education Journal, 2025)
Learning media plays an important role in attracting students' interest in learning. However, its utilization has not been optimal, resulting in low learning enthusiasm. This study aims to examine the use of interactive videos to improve critical thinking skills of grade XI students in the Al-Qur'an and Hadith subjects at MAN 2 Garut. The method used is quantitative with a quasi-experimental design. Data were collected through tests, observations, and documentation. The results showed that interactive videos received positive responses from teachers (73.3%) and students (65%), and were able to improve students' critical thinking skills (N-Gain 48%), although its effectiveness was still relatively low. Meanwhile, the control class actually experienced a decline. In conclusion, interactive videos are better than conventional media, but not yet fully effective.